The effect of addition of vegetable waste on microbial fuel cell performance. Issue 1 (February 2021) - Mulyono, T; Misto,; Nasifatul, S M
Abstract: In the past few years the fuel cell has become the centre of attention of the scientific community for the possibility of converting organic waste into electricity directly through redox reactions with the help of bacteria or enzymes. The purpose of this study was to determine the value of MFC performance due to the influence of adding vegetable waste. The soil media used is obtained from agricultural areas. The system used in the MFC is a single chamber of a vessel with a volume of 500 mL. The types of electrodes used are carbon fibres with anode thickness of 0.5 cm and cathode 1.0 cm, as well as anode diameter of 8.0 cm and cathode 8.5 cm. Vegetable wastes were given 5 mg / L each in the MFC single chamber. The results showed that the highest power was generated from a microbial fuel cell with spinach vegetable waste. The power produced is 250 mW (49 mW/cm 2 ). The incubation period for MFC can reach 30 days. Variation of the second rinse with a concentration of 499 ppm will have a pH value having a pretty good linear correlation of 0.9536 to the more electric power generated. The power produced by the MFC 6 series circuit is 1.00 mW, while the power generated by the parallel series is 0.831mW.